Discovery of BR102375, a new class of non-TZD PPARγ full agonist for the treatment of type 2 diabetes. Issue 16 (15th August 2019) - Choung, Wonken; Yang, Deokmo; Kim, Hakdo; Choi, Hyukjoon; Lee, Bo Ram; Park, Min; Jang, Su Min; Lim, Jae Soo; Kim, Woo Sik; Kim, Kyung-Hee; Chin, Jungwook; Jung, Kyungjin; et al.
Graphical abstract: Abstract: As a potential treatment of type 2 diabetes, a novel PPARγ non-TZD full agonist, compound 18 (BR102375) was identified from the original lead BR101549 by the SAR efforts of the labile metabolite control through bioisosteres approach. In vitro assessments of BR102375 demonstrated its activating potential of PPARγ comparable to Pioglitazone as well as the induction of related gene expressions. Further in vivo evaluation of BR102375 in diabetic rodent models successfully proved its glucose lowering effect as a potential antidiabetic agent, but the anticipated suppression of weight gain was not evident. The X-ray co-crystal analysis of BR102375-PPARγ LBD unexpectedly revealed binding modes totally different from those of BR101549, which was found, instead, closely resembled to those of TZD full agonists.